2017
DOI: 10.1108/jmp-08-2016-0235
|View full text |Cite
|
Sign up to set email alerts
|

Leader pride and gratitude differentially impact follower trust

Abstract: Purpose Current research suggests a positive link between followers’ perceptions of their leaders’ expression of positive emotions and followers’ trust in their leaders. Based on the theories about the social function of emotions, the authors aim to qualify this generalized assumption. The purpose of this paper is to demonstrate that followers’ perceptions of leaders’ expressions of specific positive emotions – namely, pride and gratitude – differentially influence follower ratings of leaders’ trustworthiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Kube et al (2012) showed in several experiments that when employers gave employees gifts as expressions of gratitude, monetary gifts did not increase reciprocal behavior in the form of higher productivity, whereas non-monetary gifts did. Ritzenhöfer et al (2017) found that leaders’ expressions of gratitude were associated with higher perceived benevolence and integrity. Stegan and Wankier (2018) showed that when a person’s advice is rejected, that person continues to hold higher prosocial attitudes and more helping behavior if he or she is shown appreciation.…”
Section: Studymentioning
confidence: 94%
“…Kube et al (2012) showed in several experiments that when employers gave employees gifts as expressions of gratitude, monetary gifts did not increase reciprocal behavior in the form of higher productivity, whereas non-monetary gifts did. Ritzenhöfer et al (2017) found that leaders’ expressions of gratitude were associated with higher perceived benevolence and integrity. Stegan and Wankier (2018) showed that when a person’s advice is rejected, that person continues to hold higher prosocial attitudes and more helping behavior if he or she is shown appreciation.…”
Section: Studymentioning
confidence: 94%
“…Similarly, Maher (2017) concluded that leaders with charisma influence employees to be more engaged. Ritzenhöfer et al (2017) further agreed that followers admire courageous and confident leaders and try to emulate them. The findings also echo those of Muhammad et al (2016) who concluded that to ensure employee engagement within organizations, leaders should practice charismatic leadership.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 97%
“…Also, followers of leaders with charisma admire them and try to emulate them (Bass & Riggio, 2006). They are proud to associate with а leader who is bold and courageous (Ritzenhöfer, Brosi & Welpe, 2017).…”
Section: Idealized Influence and Employee Engagementmentioning
confidence: 99%
“…Algoe et al (2008) observed that grateful leaders further express gratitude toward followers therefore communicating a pro-social, other-regarding outlook. Ritzenhöfer et al (2017) found that grateful leaders created positive situations that resulted in followers rating such leaders high in trustworthiness, benevolence and integrity (Garg, 2018).…”
Section: Gratitude Leadership and Social Intelligencementioning
confidence: 99%
“…Role of SI among teachers Waters and Stokes (2015) studied the impact of two elements, emotion gratitude and action gratitude on school leaders and found a positive impact on their "within well-being" as well as "relational well-being." Ritzenhöfer et al (2017) studied the influence of two positive emotions, namely, pride and gratitude, measured as dispositional tendencies, on organizational leaders with respect to the pro-social behaviors exhibited by them (social justice and altruism). Apart from concluding that grateful leaders recognize the contributions of others while attributing success, the findings of the study also indicated that leaders possessing grateful emotion toward organizational members could regulate their self-pride and hence could ably focus on the well-being of others (Garg, 2017a;Garg et al, 2019).…”
Section: Gratitude Leadership and Social Intelligencementioning
confidence: 99%